Environment management : for BBA 5th semester - Joshi, Rosy (Kalyani Publisher, 2010)
Environment management : for BBA 5th semester / Joshi, Rosy. -- Kolkata: Kalyani Publisher, 2010 628 J84 No. of Copies : 2